DEVELOPING THE HEALTH LITERACY OF PUBLIC HEALTH VOLUNTEERS TO ACCESS SERVICES AT COMMON ILLNESS PHARMACY, NAKHON SAWAN MUNICIPALITY - ฉายแสงมงคล ปิยฤดี (Primary Health Care Journal (Northeastern Edition), 2024)
The promotion of access to Common Illness pharmacies aims to reduce hospital congestion by enhancing the health literacy of village health volunteers, in line with the Ministry of Public Health’s policies. This research aimed to improve the health literacy of village health volunteers to facilitate access to Common Illness pharmacies in Nakhon Sawan Municipality. The study involved 11 pharmacists and 98 village health volunteers. Research tools included in-depth interviews, focus group discussions, and a health literacy promotion model. Quantitative data were analyzed using frequency distribution, percentage, mean, standard deviation, and paired samples t-test. Qualitative data were analyzed using content analysis and presented descriptively. The study found that in Phase I, 6 Common Illness pharmacies within the municipality served an average of 85.88 Gold Card patients per month per pharmacy. Outside the municipality, five pharmacies served an average of 180.5 Gold Card patients per month per pharmacy. Phase II, the health literacy promotion model, using the V-Shape Literacy Model and word-of-mouth strategies, was implemented over 12 weeks. Activities included workshops, social media engagement, and practical experience to improve access to pharmacies. Phase III, post-implementation evaluation showed that the health literacy of village health volunteers increased by 4.48 points, with a 95% confidence interval of 3.91 to 5.05. Phase IV, access to Common Illness pharmacies by Gold Card patients in the municipality increased by 149.67%. In contrast, outside the municipality, where the model was not applied, access increased by only 13.21%. In conclusion, promoting health literacy among village health volunteers using the V-Shape Literacy Model and word-of-mouth strategies effectively increased Gold Card patients’ access to Common Illness pharmacies.